Peran Kinerja Guru Bersertifikasi dalam Meningkatkan Kualitas Pembelajaran di SD Negeri Lopang Domba Kota Serang - umi hanifah; Andriani Sariwardani; Mutoharoh Mutoharoh (Journal of Innovative and Creativity, 2025)
This study aims to explore the role of certified teachers' performance in improving the quality of learning at SD Negeri Lopang Domba. The research method used is descriptive qualitative with a case study approach. The research subjects consisted of certified teachers, principals, and students at one of the public elementary schools in Serang City, Banten. Data collection techniques were conducted through in-depth interviews, direct observation, and documentation. The results showed that certified teachers have a significant role in improving lesson planning, applying more varied methods, and evaluating learning outcomes that are more structured. In addition, certification also increases teachers' motivation and professional responsibility. However, some challenges were also found, such as limitations in the application of technology and administrative burdens. The findings provide implications for the development of education policies and teacher professional development programs.